2022
DOI: 10.1111/gcb.16043
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the importance of increasing temperature and decreasing soil moisture on global ecosystem productivity using solar‐induced chlorophyll fluorescence

Abstract: The accurate assessment of the global gross primary productivity (GPP) of vegetation is the key to estimating the global carbon cycle. Temperature (Ts) and soil moisture (SM) are essential for vegetation growth. It is acknowledged that the global Ts has shown an increasing trend, yet SM has shown a decreasing trend. However, the importance of SM and Ts changes on the productivity of global ecosystems remains unclear, as SM and Ts are strongly coupled through soil‐atmosphere interactions. Using solar‐induced ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 90 publications
0
22
0
Order By: Relevance
“…Our research found that climatic factors have a greater influence on the spatial distribution of SOCS than other environmental factors (i.e., terrain, land use, and land cover [LULC], organism and soil factors). this finding could be attributed to the sensitivity of SOC decomposition and accumulation to climate change (e.g., warmer temperatures and less precipitation) (Dang et al, 2022; Davidson & Janssens, 2006). Indeed, litter produced during vegetation growth is the main source of soil carbon input (Stuart Chapin Iii et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Our research found that climatic factors have a greater influence on the spatial distribution of SOCS than other environmental factors (i.e., terrain, land use, and land cover [LULC], organism and soil factors). this finding could be attributed to the sensitivity of SOC decomposition and accumulation to climate change (e.g., warmer temperatures and less precipitation) (Dang et al, 2022; Davidson & Janssens, 2006). Indeed, litter produced during vegetation growth is the main source of soil carbon input (Stuart Chapin Iii et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…VPD and SM are commonly used indicators for atmosphere and soil dryness, respectively [ 42 , 43 , 44 ]. A significant effect by drought on vegetation greenup development was observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The GLEAM v3.5a dataset was produced by combining satellite and reanalysis data, which provides temporally/spatially continuous SM at spatial resolution of 0.25° (~25 km), spanning from 1980 to 2020. The overall performance accuracy of GLEAM SM products is considerably high [ 43 ]. The mean values in spring were calculated for all climatic factors.…”
Section: Methodsmentioning
confidence: 99%
“…For example, compared with VPD, SM is the dominant driver of dryness stress on ecosystem production that is characterized by SIF [43]. Similarly, using SIF as a proxy for GPP, Dang et al [44] demonstrated that SM plays a more important role, and SIF is very sensitive to aridity gradients in arid and semi-arid ecosystems. The results coincided with our reports.…”
Section: Pros and Cons Of F760tot For Drought Monitoringmentioning
confidence: 99%